(untitled) (REMUNOM, 2024)
Higher education institutions often face the challenge of student dropout, both in public and private institutions, which causes economic, cultural, and social damage. In this context, this study sought to outline the sociodemographic profile and identify the probable reasons for university students dropping out of the Physical Education course at a public university in Bahia. This is an observational, cross-sectional, descriptive study with a quantitative approach. A sociodemographic questionnaire and the Scale of Reasons for Dropping Out of Higher Education were used. The sample consisted of 99 students enrolled in the Physical Education course. 47.5% were aged between 21 and 25, 61.6% were male, 36.4% self-declared as brown, 94.9% were single, 96.0% had no children and 69.1% had a family income of between one and three minimum wages. The majority rated the possibility of dropping out as “very weak”, however, the factors “lack of support” (11.7%) and “career” (8.6%) were the most frequently rated as “very strong” reasons for dropping out. This data highlights the importance of providing support to university students during the period of adaptation to the academic environment, as well as pedagogical support, aspects that can be decisive for staying and completing the course.